Urgensi Nilai-Nilai Pendidikan dalam Salat terhadap Pembentukan Keluarga yang Sakinah di Era 5.0 - Munawarah, Madinatul; Taufikurahman, Muhammad (Jurnal Pendidikan Islam, 2024)
Prayer is not just an Islamic religious ritual that only has implications for life in the afterlife, but also influences various aspects of life, one of which is married life. This research aims to describe the educational values contained in prayer which have big implications in forming a harmonious family and what Muslims aspire to, namely a sakinah family. This research is library research whose sources are obtained from various types of literature. Rasulullah was a person who prayed a lot, it is also narrated that Rasulullah was the kindest figure towards his family so it is appropriate that Rasulullah's family be used as an example for Muslim families in all times, even in this 5.0 era which is full of challenges. The importance of praying is a clear illustration that in prayer there are values that have a big influence in forming a Sakinah family, including: (1) Prayer makes you closer to Allah SWT, (2) Prayer educates to maintain cleanliness, (3) Prayer makes you closer to Allah SWT, (2) Prayer educates to maintain cleanliness, (3) Prayer makes the soul peaceful, (4) Prayer educates to maintain unity and unity, (5) Prayer educates to be orderly (6) Prayer makes you discipline, (7) Prayer educates to become a person who dares to remember the truth.